Thai Guideline for Nuclear Medicine Investigations of Neurocognitive Disorders: Nuclear Medicine Society of Thailand, the Neurological Society of Thailand, and Thai Medical Physicist Society Collaboration - Tawika Kaewchur; Tanyaluck Thientunyakit; Wichana Chamroonrat; Benjapa Khiewvan; Peerapon Kiatkittikul; Nantaporn Wongsurawat; Chanisa Chotipanich; Yuttachai Likitjaroen; Vorapun Senanarong; Panya Pasawang; Tanawat Sontrapornpol; Nucharee Poon-iad; et al. (Diagnostics, 2024)
Nuclear medicine investigations play a significant role in diagnosing dementia, mainly using imaging techniques such as positron emission tomography (PET) and single-photon emission computed tomography (SPECT). By providing functional and molecular data via brain imaging, nuclear medicine investigations offer valuable insights that complement clinical evaluations and structural imaging in the early detection, diagnosis, and differentiation of various types of dementia, leading to more accurate diagnosis and personalized treatment planning. Therefore, the Nuclear Medicine Society of Thailand, the Neurological Society of Thailand, and the Thai Medical Physicist Society have collaborated to establish these practical nuclear medicine investigation guidelines aiming to (1) identify the role of nuclear medicine studies in patients with neurocognitive disorders; (2) assist referrers in requesting the most appropriate procedure for diagnosis of each type of neurocognitive disorders; and (3) identify scientific evidence that is useful to assisting nuclear medicine professionals in recommending, performing, interpreting, and reporting the results of nuclear medicine investigations in patients with neurocognitive disorders.